2013
DOI: 10.3390/ijms14046571
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Fingerprint of High Grade Serous Ovarian Cancer Reflects Its Fallopian Tube Origin

Abstract: High grade serous ovarian cancer (HGSC), the most lethal and frequent type of epithelial ovarian cancer (EOC), has poor long term prognosis due to a combination of factors: late detection, great metastatic potential and the capacity to develop resistance to available therapeutic drugs. Furthermore, there has been considerable controversy concerning the etiology of this malignancy. New studies, both clinical and molecular, strongly suggest that HGSC originates not from the surface of the ovary, but from the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 95 publications
0
33
0
Order By: Relevance
“…The best evidence for this is from women with germline BRCA mutations. These advances have been supported by numerous morphological and molecular biological studies and studies in animal models [1][2][3][4][5][6][7][8]. It is essential for all types of biological studies of cancer to have a firm foundation in histopathology to provide the requisite context.…”
Section: Introductionmentioning
confidence: 99%
“…The best evidence for this is from women with germline BRCA mutations. These advances have been supported by numerous morphological and molecular biological studies and studies in animal models [1][2][3][4][5][6][7][8]. It is essential for all types of biological studies of cancer to have a firm foundation in histopathology to provide the requisite context.…”
Section: Introductionmentioning
confidence: 99%
“…The fallopian tube as the site of origin of ''ovarian cancer'' was proposed by Dutch investigators (18) after several studies of prophylactic salpingo-oophorectomy specimens from high-risk women revealed small tubal carcinomas (1,16). There is now a stream of reports worldwide that confirm and expand on these data with morphologic and molecular studies as well as observations in animal models (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…1 The pathogenesis of epithelial ovarian cancer represents a field of intense research, especially after the recognition that differences in histology may reflect differences in tumor development. 2 Furthermore, potential risk factors, such as endometriosis, 3 ovarian cysts, 3 and certain genetic deficiencies have been identified, 2 whereas thyroid disease has been recently linked epidemiologically to the development of ovarian cancer. 3 In addition, it is known that ovarian cyst formation may be more frequent in women with primary hypothyroidism 4 and in experimentally hypothyroid animals exposed to stimulation with gonadotropins.…”
mentioning
confidence: 99%